Utility of prenatal MRI in the evaluation and management of fetal ventriculomegaly. (November 2018) - Katz, Jenna; Chock, Valerie; Davis, Alexis; Blumenfeld, Yair; Hahn, Jin; Barnes, Patrick; Barth, Richard; Rubesova, Erika; Hintz, Susan
Abstract Objective Fetal ventriculomegaly may occur in isolation or as part of a broader syndrome. We aimed to determine the added value of magnetic resonance imaging (MRI) for informing the pre-natal and postnatal care of pregnancies complicated by ventriculomegaly (VM). Study design Retrospective analysis of all cases of prenatally diagnosed VM referred to the fetal center at Lucile Packard Children's Hospital Stanford 1/1/2009–6/1/2014 were reviewed. Ultrasound (US) and MRI findings were reviewed, and the added yield of MRI evaluated. Results A total of 91 cases of fetal VM were identified and 74 (81%) underwent MRI. In 62/74 (84%) cases, additional CNS or non-CNS findings, not seen on US, were discovered on MRI, of which 58 were CNS-related. Forty-six (62%) of the additional findings were considered clinically relevant, of which 45 were CNS-related. Conclusion Fetal MRI identifies additional, clinically relevant CNS and non-CNS findings in a majority of cases of VM following initial US.